DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Xoshimova Nilufar; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Abstract Teaching  foreign  languages  to  young  learners  is  both  a  rewarding  and challenging task. While children have a natural ability to acquire new languages, the teaching  process  involves  several  difficulties.  This  article  explores  the  common challenges faced by language teachers when working with young learners and provides insights into how these issues can be addressed effectively.